Réécriture des pièces de Shakespeare : l’enjeu de la modernité ? - Estelle Rivier (Revue LISA)
Shakespeare’s works remain a reference when artists — either playwrights or stage professionals — aim at philosophising on human nature. These artists use the Shakespearean material to give vent to their own imagination and critical approach to the world they live in. Not surprisingly, Shakespeare’s plays have constantly been adapted on stage and in the cinema to comment upon contemporary facts and to voice either political or social concerns. But the same plays have also been the pretexts for other plays, written in modern English so as to serve new prospects. This study is based on the work of three twentieth-century writers – Arnold Wesker, Edward Bond and Tom Stoppard – who rewrote Shakespearean plays: The Merchant of Venice (The Merchant, 1977), King Lear (Lear, 1972) and Hamlet (Rosencrantz and Guildenstern are Dead, 1967). This article explores the way these plays were elaborated with reference to the original versions and why their authors decided to adapt the Elizabethan text.